PERENCANAAN KAPASITAS PESANAN BONEKA CUSTOM DI PD MOTEKAR BANDUNG MELALUI PERANCANGAN LINTASAN PERAKITAN BONEKA RUTIN - AGATHA WILLIM NIM 13414036, DISA
PD Motekar Bandung is one of the Sukamulya cloth dolls SMEs which serves the making of ordered demand. Their products consists of 3 types: bears, bears head, and custom pillow. However, up until now the demand for fixed consumers (type 1 and 2) which counted only 2750 units per week can’t always be fulfilled, whereas the orders from variable consumers (type 3) which counted as much as 4300 units per week can always be fulfilled. Furthermore, the smoothness index (SI) of bears, bears head, and custom pillow assembly line are 77.74, 59.36, and 120.64 with the utilization of 6, 5, and 4 workstations. Based on this existing facts, this dissertation will do a standardization to create doll assembly lines for gaining the information of custom demand capacity so the fixed demand can be fulfilled every week. A mathematical model with workstation amount minimization as the objective is used in this dissertation. The result of this model results is work elemen assignment into workstation within backward and forward. To obtain a maximum result for the company, the objective function and constraints were added to minimize SI in order to meet company’s characteristics. The required inputs are the data of work elements and its duration, number of available work stations, takt time, and precedence diagrams. After that, the computation for standardized assembly line was done with the help of LINGO for three types of dolls. Then, the capacity of custom pillow production was obtained. Based on the result, the fulfillment of fixed consumer demand was achieved. Furthermore, there will be an increasing in the production capcaity of custom pillows by 36.5% to 5460 units. The SI values for each doll type become 22.14, 10.94, and 7.5 with the utilization of 4, 3, and 3 workstations. Therefore, proposed resources utilization becomes more optimal. IDR 2.755.000 is required for investment cost as to support the implementation of relayout activity. Hence, proposed solutions are proven to achieve better condition from existing ones.